La conciencia colectiva como chr(38)quot;conjunto de fenómenoschr(38)quot;: el programa de la fenomenología en el chr(38)quot;Durkheim objetivistachr(38)quot; = Collective consciousness as a chr(38)quot;collection of phenomenachr(38)quot;: the program of phenomenology in the chr(38)quot;objectivist Durkheimchr(38)quot; - Belvedere, Carlos (Civitas - Revista de Ciências Sociais)
My aim is to disclose a programmatic convergence between Durkheim and Husserl in three different levels, thematic, methodological and ontological. In order to do so, I will carry out a phenomenological reading of The Rules of the Sociological Method in search of some core ideas of The Crisis of European Sciences and Transcendental Phenomenology and of The Origin of Geometry. I will also show, in accordance with Cathesian Meditations, that the sociological method is, in as much as phenomenology, a carthesian way. Then I will explain that Durkheim’s methodological and ontological stances present the same circularity as Husserl’s in Marion’s analysis. Then I will put on view that the way in which Durkheim faces it situates him in the phenomenology of the natural attitude undertaken by Schutz. Finally I will illustrate how Durkheim, just as Galileo according to Crisis…, is at a time a disclosing and a concealing genius and that’s the reason why he lets go the best of his social phenomenology, holding to a thoughtless anthropomorphism and to metaphysical dogmas which he didn’t get to put into brackets